Aspek hukum perizinan dan legalitas lembaga pendidikan pesantren di indonesia - Najiya, Usluki (Maliki Interdisciplinary Journal, 2025)
This study examines the legal aspects related to the licensing and legitimacy of Islamic boarding schools (pesantren) in Indonesia, emphasizing the constitutional basis, registration process, and challenges in implementing Islamic boarding school regulations. As the oldest Islamic educational institutions in Indonesia, Islamic boarding schools play a crucial role in enhancing the nation’s intelligence and building community character. However, legal developments indicate that Islamic boarding schools have only recently received official recognition through Law Number 18 of 2019 concerning Islamic Boarding Schools and various other related regulations. This study applies a normative juridical method with a statutory and conceptual approach to examine the status of Islamic boarding schools as legal entities. The study’s findings indicate that Islamic boarding schools have a solid legal basis within the national education framework, although their implementation still faces bureaucratic challenges, minimal socialization, and cultural resistance among traditional Islamic boarding schools. Therefore, collaboration between the government and Islamic boarding schools is needed to improve the legal management and administration of Islamic boarding schools as an important part of the national education system.